Method for improving functional durability of toy building element

By heat treatment of toy building components and combined with impact-resistant amorphous materials, the problem of lower stress relaxation characteristics after the increase of impact-resistant modifiers in the prior art is solved, and the effect of improving functional durability and extending service life is achieved. .

CN119403673APending Publication Date: 2025-02-07LEGO AS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380048650.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

After adding impact modifiers to existing toy building components, the impact toughness is improved but the stress relaxation characteristics are reduced, making it difficult to meet the durable construction needs.

Method used

Its functional durability is improved by heat treatment of the toy building element, especially heat treatment at a temperature of at least 40°C for at least 15 minutes. The method combines an impact-modified amorphous material with an enthalpy relaxation of at least 0.3 J/g and a maximum shrinkage of 0.2%.

Benefits of technology

The toy building components are realized to improve functional durability, allowing them to maintain assembly capabilities more stably, extend product service life, and provide stable press fit functions in pre-built assembly lines without glue or other permanent interfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403673A_ABST
    Figure CN119403673A_ABST
Patent Text Reader

Abstract

The present invention relates to a method of manufacturing a toy building element with improved functional durability made of an impact modified amorphous material having an enthalpy relaxation of at least 0.3 J / g (e.g. In the range of 0.3 J / g to 4 J / g) and a shrinkage of at most 0.2%. The invention also relates to a toy building element with improved functional durability made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g (e.g. In the range of 0.3 J / g to 4 J / g) and a shrinkage of at most 0.2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for producing a toy building element with increased functional durability, the toy building element being made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4 J / g, and a shrinkage of at most 0.2%. The invention also relates to a toy building element with increased functional durability, the toy building element being made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4 J / g, and a shrinkage of at most 0.2%. Background Art

[0002] Toy building elements have been on the market for many years. They are usually manufactured by injection molding of polymer materials. The injection molding process is carried out at the temperature of the polymer material in order to obtain toy building elements made of amorphous material. Usually, the temperature of the polymer material in the injection molding barrel is above the melting temperature. The melt enters the cooler mold in order to solidify the material. The mold temperature can be above or below the glass transition temperature (Tg) of the polymer material. Temperatures below Tg favor the transition to an amorphous final material.

[0003] It is well known that the impact toughness of polymer materials needs to reach a sufficient level to meet the requirements of product safety and play experience, so that durable toy building blocks can be produced, for example, without breaking when dropped on the floor or stepped on by an adult. Satisfactory impact toughness is particularly important for objects with complex geometries, such as traditional The geometry of the block is provided with a knob on the upper side and / or a complementary tube on the lower side.

[0004] Some toy building elements are manufactured as building blocks, i.e., the purpose of such blocks is to build larger, more durable buildings that can be played with and moved from one place to another without the blocks falling apart. Coupling force, which represents the amount of effort required by a person to assemble and separate the blocks, is an important property of toy building elements. Coupling force is the result of the interconnected overlap between areas of a toy building element, such as a knob and a complementary tube. It is affected by, for example, material stiffness, friction, creep and stress relaxation. Coupling force is a very important property of building blocks in order to maintain the functional durability of the interconnected building blocks in a durable building.

[0005] Unfortunately, adding impact modifiers to polymeric materials can compromise the polymeric material's stress relaxation properties, which are necessary to maintain the functional durability of interconnected toy building elements in durable constructions.

[0006] It is therefore necessary to provide a polymer material which has, on the one hand, a sufficiently high impact toughness and, on the other hand, also a satisfactory stress relaxation, so that toy building elements for durable constructions can be produced.

[0007] The inventors of the present invention have overcome this challenge and are now able to manufacture toy building elements from impact-modified amorphous polymer materials having satisfactory impact toughness and satisfactory functional durability, thereby allowing the construction of durable buildings. Summary of the invention

[0008] The invention relates to a method for producing a toy building element with increased functional durability, the toy building element being made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4 J / g, and a shrinkage of at most 0.2%. The invention also relates to a toy building element with increased functional durability, the toy building element being made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4 J / g, and a shrinkage of at most 0.2%.

[0009] The inventors of the present invention have surprisingly found that by heat treating toy building elements it is possible to obtain toy building elements with improved functional durability, i.e. toy building elements with an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4 J / g, and a shrinkage of at most 0.2%. This improving effect can be seen after heat treating the toy building elements for at least 15 minutes at a treatment temperature of at least 40°C, wherein the upper limit of the heat treatment temperature is at most 20°C below the onset temperature of the glass transition temperature (Tg) of the impact-modified amorphous material.

[0010] The toy building elements manufactured by the method according to the invention have an increased functional durability, with an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4.0 J / g, and a shrinkage of at most 0.2%. The increased functional durability makes it possible to assemble the toy building elements to build advanced and strong buildings, with an increased ability to maintain the assembly, without the blocks breaking apart or losing their press-fit function over time.

[0011] The increased functional durability can also extend the useful life of products that rely on press-fit functionality. This is not only related to their stability when connected to each other, but also to their reusability. In addition, the increased functional durability also allows certain press-fits to have stable functionality when assembling parts in a pre-built assembly line without the need for glue, welding or other permanent interface assembly methods. This is possible because the heat treatment of the toy building elements according to the present invention can control the instant and press-fit functionality over time.

[0012] In a first aspect, the invention relates to a method for producing a toy building element with increased functional durability, the toy building element being made from an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4 J / g, and a shrinkage of maximum 0.2%.

[0013] In a second aspect, the invention relates to a toy building element with increased functional durability, made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g (e.g. in the range of 0.3 J / g to 4 J / g) and a shrinkage of maximum 0.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Shown are stress relaxation measurements at 30°C and 1% strain for 48 hours for rPET containing 10 wt% PARALOID EXL and 2.5 wt% ELVALOY PTW with and without heat treatment of injection molded parts at 50°C for 8 hours.

[0015] Figure 2 Shown are normalized stress relaxation results for stress relaxation measurements of rPET containing 10 wt% PARALOID EXL and 2.5 wt% ELVALOY PTW at 30°C and 1% strain for 48 hours with and without heat treatment of injection molded parts at 50°C for 8 hours.

[0016] Figure 3 The relative stress retention of rPET containing 10 wt% PARALOID EXL and 2.5 wt% ELVALOY PTW at 30°C and 1% strain for 48 hours for injection molded parts at 50°C for different heat treatment times is shown.

[0017] Figure 4 The relative stress retention at 30°C and 1% strain for 48 hours for the impact-modified PMMA, impact-modified rPET, unmodified PETT and unmodified PETG materials in Table 1 is shown with and without heat treatment of the injection molded components at 50°C or 60°C for 24 hours.

[0018] Figure 5 The relative stress retention at 30°C and 1% strain for 48 hours for rPET containing different concentrations of impact modifiers with and without heat treatment of injection molded parts at 50°C for 24 hours is shown.

[0019] Figure 6The impact toughness of pure rPET and rPET containing different concentrations of impact modifiers is shown for injection molded parts with and without heat treatment at 50°C for 24 hours.

[0020] Figure 7 Shown are the impact toughness and enthalpy relaxation of rPET containing 10 wt% PARALOIDE XL and 2.5 wt% ELVALOY PTW during heat treatment of injection molded parts at 60°C for 24 hours.

[0021] Figure 8 Shown is the percent shrinkage of rPET containing 10 wt% PARALOID EXL and 2.5 wt% ELVALOY PTW after heat treating the injection molded parts for 24 hours at different heat treatment temperatures.

[0022] Fig. 9 Shown is the Charpy V-notch impact toughness of rPET containing 10 wt% PARALOID EXL and 2.5 wt% ELVALOY PTW after heat treating the injection molded parts for 24 hours at different heat treatment temperatures.

[0023] Fig.10 Shown is the relative stress retention of rPET containing 10 wt% PARALOID EXL and 2.5 wt% ELVALOY PTW after heat treating injection molded parts for 24 hours at different heat treatment temperatures.

[0024] Fig.11 shows the traditional box-shaped 2*4 blocks. DETAILED DESCRIPTION

[0025] A first aspect of the invention relates to a method for producing a toy building element with increased functional durability, the toy building element being made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g (e.g. in the range of 0.3 J / g to 4 J / g) and a shrinkage of at most 0.2%, the method comprising the following steps:

[0026] a) providing a resin comprising a polymer and an impact modifier,

[0027] b) processing resins to produce amorphous toy building elements,

[0028] c) heat-treating the amorphous toy building elements at a heat-treating temperature of at least 40°C for at least 15 minutes, and

[0029] d) cooling the heat-treated toy building element to ambient temperature,

[0030] The upper limit of the heat treatment temperature in step c is 20° C. lower than the onset temperature of the glass transition temperature (Tg) of the impact-modified amorphous material.

[0031] The term "toy building element" as used herein includes conventional toy building elements in the form of box-shaped building blocks, which are provided with a knob on the upper side and a complementary tube on the lower side. Fig.11 The conventional box-shaped toy building block was first disclosed in U.S. Pat. No. 3,005,282 and is and The term also includes other similar box-shaped building blocks that are manufactured by companies other than the LEGO Group and therefore sold under trademarks other than the LEGO trademark.

[0032] The term "toy building element" also includes other types of toy building elements which are provided with a knob on the upper side and / or with a complementary tube on the lower side, which may form part of a toy building set which generally comprises a plurality of building elements which are compatible with each other and can therefore be connected to each other. Such toy building sets are also sold under the LEGO trademark, e.g. piece( bricks), Mechanical Group( Technic) and Some of these toy building sets include toy building figures, e.g. Minifigures( Minifigures) (see, for example, US 05 / 877,800) have a complementary tube on their underside so that the figure can be connected to other toy building elements in a toy building set. Such toy building figures are also included in the term "toy building element". The term also includes similar toy building elements that are produced by other companies than the LEGO Group and are therefore sold under other trademarks than the LEGO trademark.

[0033] Toy building elements come in a wide variety of shapes, sizes and colors. Block and One difference between the two is the size, All block sizes are Twice the size of a block. Traditional box shape with 4*2 knobs on the top The dimensions of the toy building block are about 3.2 cm long, about 1.6 cm wide, and about 0.96 cm high (excluding the knobs), and the diameter of each knob is about 0.48 cm. In contrast, the upper side has 4*2 knobs. The dimensions of the block were approximately 6.4 cm in length, 3.2 cm in width, and 1.92 cm in height (excluding the knobs), with each knob having a diameter of approximately 0.96 cm.

[0034] The toy building elements manufactured by the method of the present invention have improved functional durability. The term "functional durability" as used herein refers to the stability of the stiffness of the material during stress relaxation, i.e., functional durability. In practice, it can be regarded as a measure of the coupling force. An acceptable functional durability is a stress loss of 50% within 48 hours at 35°C measured in a 1% strain relaxation test. A preferred functional durability is a stress loss of 20% to 50%, and a particularly preferred functional durability is a stress loss of 20% or less.

[0035] The toy building elements manufactured by the method of the present invention are made of an impact-modified amorphous material. The term "impact-modified material" refers to a polymer material, wherein the polymer is mixed with at least one impact modifier in an amount that increases the impact toughness of the material. The impact toughness is measured using the Charpy V-notch test according to ISO 179-1. The acceptable impact toughness of the durable material according to the present invention after heat treatment at 50°C for 24 hours is generally in the range of 5 kJ / m2-100 kJ / m2. Preferred impact toughness is 8 kJ / m2-50 kJ / m2, and particularly preferred impact toughness is 10 kJ / m2-30 kJ / m2.

[0036] The term "enthalpic relaxation" as used herein refers to the integration of the endothermic peak after the glass transition temperature (Tg) measured by differential scanning calorimetry (DSC). The method is described in "Progress of the Royal Society of Chemistry (RSC.Advances)" 2019, 9, 14209-14219 for 20 mg flat cut samples on a DSC autosampler (Q2000, TAInstruments, the United States).

[0037] The enthalpy relaxation must be at least 0.3 J / g. Typically, the enthalpy relaxation is in the range of 0.3 J / g to 4 J / g, for example in the range of 0.5 J / g to 4 J / g, but in a preferred embodiment, the enthalpy relaxation is in the range of 1 J / g to 3 J / g.

[0038] As used herein, the term "shrinkage" refers to the average value of the length and width of an ISO 527-1BA tensile element relative to the initial dimensions, according to the following formula:

[0039]

[0040] Where t=x is the size after a period of heat treatment, and t=0 is the initial size of the component.

[0041] The toy building element of the invention is characterised by its functional durability, stress relaxation, enthalpy relaxation, shrinkage and impact toughness. In order to understand the invention it is important to understand the nature of these terms including their relationship.

[0042] Functional durability refers to the stiffness of a material during stress relaxation, which is directly measured by a stress relaxation test. When a toy building element is heat treated according to the present invention, stress relaxation is greatly improved by causing physical aging. Due to physical aging, impact toughness is reduced. For example, this correlation is explained in "Progress of the Royal Society of Chemistry (RSC.Advances)" 2019, 9, 14209-14219. Shrinkage is a measure of the dimensional stability of a toy building element. Finally, enthalpy relaxation measures the degree of physical aging, which can be used to characterize any geometric shape, where stress relaxation and impact toughness tests require standardized geometric shapes. This must be able to characterize the degree of physical aging of any geometric shape, understand its impact toughness and stress relaxation characteristics (see, for example, LCE Struk, Physical aging in plastics and other glassy materials, "Polym. Eng. Sci. " 17 (3) (March 1977) 165-173).

[0043] The term "amorphous material" refers to a polymer material having a crystallinity of 20% or less. The crystallinity can be calculated using the following formula:

[0044] % crystallinity = [(ΔH f -ΔH c ) / ΔH f °]*100%

[0045] The value of ΔH f , ΔH c and ΔH f The method for measuring ° is described in “Kong, Y.; Hay, J. The measurement of the crystallinity of polymers by DSC”, Polymer, 2002, 43, 3873-3878, for 20 mg flat-cut samples on a DSC autosampler (Q2000, TA Instruments, USA).

[0046] In step a), a resin is provided, which comprises a polymer and an impact modifier.

[0047] In one embodiment, the amount of polymer in the resin is at least 50 weight % based on the total weight of the resin. In other embodiments, the amount of polymer in the resin is at least 60 weight % based on the total weight of the resin. In a preferred embodiment, the amount of polymer in the resin is at least 70 weight %, such as at least 85 weight % based on the total weight of the resin, or at least 90 weight % based on the total weight of the resin.

[0048] In another embodiment, the amount of polymer in the resin is in the range of 50 wt% to 99 wt% based on the total weight of the resin. In other embodiments, the amount of polymer in the resin is in the range of 60 wt% to 97 wt% or 70 wt% to 95 wt% based on the total weight of the resin. In a preferred embodiment, the amount of polymer in the resin is in the range of 75 wt% to 95 wt%, such as 80 wt% to 95 wt%, based on the total weight of the resin.

[0049] The polymer in the resin may be a bio-based polymer, a hybrid bio-based polymer or a petroleum-based polymer or a mixture thereof.

[0050] The term "bio-based polymer" as used herein refers to a polymer prepared by chemical or biochemical polymerization of monomers derived from biomass. Bio-based polymers include polymers prepared by polymerization of one monomer derived from biomass, and polymers prepared by polymerization of at least two different monomers derived from biomass.

[0051] In a preferred embodiment, the bio-based polymer is prepared by chemical or biochemical polymerization of monomers, which are derived from biomass.

[0052] The bio-based polymer according to the present invention comprises

[0053] - polymers produced by biochemical polymerization (ie for example using microorganisms). The monomers are produced using biomass as substrate.

[0054] - The polymers are prepared by chemical polymerization, ie by chemical synthesis. The monomers are prepared using biomass as substrate.

[0055] In some embodiments, the bio-based polymer is prepared by biochemical polymerization. In other embodiments, the bio-based polymer is prepared by chemical polymerization. In still other embodiments, the bio-based polymer is prepared by biochemical or chemical polymerization. The bio-based polymer can also be prepared by a combination of biochemical polymerization and chemical polymerization, for example, in the case where two monomers are combined into a dimer through a biochemical reaction pathway and then the dimer is polymerized using a chemical reaction.

[0056] Bio-based polymers also include polymers having the same molecular structure as petroleum-based polymers, but which are prepared by chemical and / or biochemical polymerization of monomers derived from biomass.

[0057] As used herein, the term "petroleum-based polymer" refers to polymers prepared by the chemical polymerization of monomers derived from petroleum, petroleum byproducts, or petroleum-derived feedstocks.

[0058] As used herein, the term "hybrid bio-based polymer" refers to a polymer prepared by polymerizing at least two different monomers, wherein at least one monomer is derived from biomass and at least one monomer is derived from petroleum, a petroleum byproduct, or a petroleum-derived feedstock. The polymerization process is typically a chemical polymerization process.

[0059] The mixed bio-based polymer can also be characterized by its bio-based carbon content per total carbon content. The term "bio-based carbon" as used herein refers to carbon atoms derived from biomass used as a substrate in the preparation of monomers, which form part of the bio-based polymer and / or mixed bio-based polymer. The content of bio-based carbon in the mixed bio-based polymer can be determined by the carbon-14 isotope content specified in ASTM D6866 or CEN / TS 16137 or equivalent schemes.

[0060] In some embodiments, the content of bio-based carbon in the mixed bio-based polymer is at least 25%, such as at least 30% or at least 40%, based on the total carbon content of the mixed bio-based polymer. In other embodiments, the content of bio-based carbon in the mixed bio-based polymer is at least 50%, such as at least 60%, such as at least 70%, such as at least 80%, based on the total carbon content of the mixed bio-based polymer.

[0061] In some embodiments, the content of bio-based carbon in the polymer is at least 25% based on the total carbon content in the polymer. In other embodiments, the content of bio-based carbon in the polymer is at least 50%, such as at least 60%, such as at least 70%, preferably at least 80%, more preferably at least 90%, even more preferably at least 95%, based on the total carbon content. In the most preferred embodiment, the content of bio-based carbon in the polymer is 100% based on the total carbon content in the polymer.

[0062] In some embodiments, the content of bio-based carbon in the resin is at least 25% based on the total carbon content in the resin. In other embodiments, the content of bio-based carbon in the resin is at least 50%, such as at least 60%, such as at least 70%, preferably at least 75%, more preferably at least 80%, even more preferably at least 85%, based on the total carbon content in the resin. In the most preferred embodiment, the content of bio-based carbon in the resin is 90% based on the total carbon content in the resin.

[0063] The terms "bio-based polymer," "hybrid bio-based polymer," and "petroleum-based polymer" also include recycled polymers and recycled materials comprising "bio-based polymer," "hybrid bio-based polymer," and "petroleum-based polymer."

[0064] The term "recycled material" as used herein refers to a material obtained by processing a resin containing a recycled polymer. The recycled polymer is obtained from waste material. The waste material can be a mechanical recycled material or a chemical recycled material.

[0065] "Mechanical recycled material" refers to material that has been recovered through mechanical recycling of materials. Mechanical recycling involves only mechanical processes such as grinding, washing, separation, drying, re-granulation and compounding. In a typical recycling process, waste materials are collected and washed to remove contaminants. The clean plastic is then ground into flakes that can be compounded and granulated or reprocessed into pellets.

[0066] "Chemically recycled materials" include materials obtained by pyrolysis, chemical depolymerization, solvent dissolution, or any other suitable chemical recovery process.

[0067] "Pyrolysis" means that the material is broken down into crude oil at high temperatures in the absence of oxygen. New crude polymers can then be made from the resulting oil through known polymerization processes.

[0068] "Chemical depolymerization" refers to the process of using chemical reagents to decompose polymers into monomers, monomer mixtures or their intermediates. New original polymers can be prepared by polymerization of monomers.

[0069] "Solvent dissolution" refers to the use of a solvent to selectively extract the polymer. The extracted polymer is recovered by precipitation of the polymer or by evaporation of the solvent. The polymer chains and structure are not destroyed.

[0070] The term "recycled polymer" refers to polymers contained in mechanically recovered waste or polymers chemically recovered from waste in a solvent dissolution process. The term also refers to virgin polymers produced in a pyrolysis recovery process or a chemical depolymerization recovery process. When the term refers to virgin polymers, it also includes polymers in which only one or two monomers are recovered by pyrolysis or chemical depolymerization.

[0071] In some embodiments, the resin comprises a mechanically regenerated polymer. In other embodiments, the resin comprises a mechanically regenerated polymer and a bio-based polymer. In other embodiments, the resin comprises a mechanically regenerated polymer and a mixed bio-based polymer. In yet other embodiments, the resin comprises a mechanically regenerated polymer and a petroleum-based polymer. In other embodiments, the resin comprises a mechanically regenerated polymer, a bio-based polymer, and a petroleum-based polymer. In other embodiments, the resin comprises a mechanically regenerated polymer, a mixed bio-based polymer, and a petroleum-based polymer. In other embodiments, the resin comprises a mechanically regenerated polymer, a bio-based polymer, and a mixed bio-based polymer. In other embodiments, the resin comprises a mechanically regenerated polymer, a bio-based polymer, a mixed bio-based polymer, and a petroleum-based polymer.

[0072] In some embodiments, the amount of mechanically regenerated polymer in the resin is at least 10 wt %, such as at least 20 wt %, or such as at least 30 wt %, such as at least 40 wt %, or such as at least 50 wt %, based on the total weight of the resin. In other embodiments, the amount of mechanically regenerated polymer in the resin is at least 60 wt %, such as at least 70 wt %, or such as at least 75 wt %, such as at least 80 wt %, or such as at least 85 wt %, based on the total weight of the resin.

[0073] In some embodiments, the polymer comprises chemically recycled monomers. In other embodiments, the polymer comprises chemically recycled monomers and bio-based monomers. In other embodiments, the polymer comprises chemically recycled monomers and mixed bio-based monomers. In other embodiments, the polymer comprises chemically recycled monomers and petroleum-based monomers. In other embodiments, the polymer comprises chemically recycled monomers, bio-based monomers, and petroleum-based monomers. In other embodiments, the polymer comprises chemically recycled monomers, bio-based monomers, and mixed bio-based monomers and petroleum-based monomers. In other embodiments, the polymer comprises chemically recycled monomers, bio-based monomers, and mixed bio-based monomers. In other embodiments, the polymer comprises chemically recycled monomers, bio-based monomers, mixed bio-based monomers, and petroleum-based monomers.

[0074] In some embodiments, the amount of chemically regenerated monomers in the polymer is at least 10 wt %, such as at least 20 wt %, or such as at least 30 wt %, such as at least 40 wt %, or such as at least 50 wt %, based on the total weight of the polymer. In other embodiments, the amount of chemically regenerated monomers in the polymer is at least 60 wt %, such as at least 70 wt %, or such as at least 80 wt %, such as at least 90 wt %, or such as at least 95 wt %, based on the total weight of the polymer.

[0075] In a preferred embodiment, the polymer is selected from the group consisting of polyesters, polyacrylates and polystyrenes.

[0076] In one embodiment, the polymer in the resin is a polyester. The term "polyester" as used herein includes any polymer in which the monomers are bonded via ester bonds. In particular, the term includes PET polyesters and modified PET polyesters and mixtures thereof.

[0077] As used herein, the term "PET polyester" includes any polymer prepared by polymerizing the monomers ethylene glycol and terephthalic acid.

[0078] The term "modified PET polyester" as used herein includes any PET polyester in which the terephthalic acid monomer or the ethylene glycol monomer is replaced by another diacid monomer or diol monomer, respectively.

[0079] - modifying the modified PET polyester by replacing all or part of the terephthalic acid groups of the PET polyester with a diacid monomer selected from the group consisting of adipic acid, succinic acid, isophthalic acid, furandicarboxylic acid, phthalic acid, 4,4'-biphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid and mixtures thereof; and / or

[0080] - modifying the modified PET polyester by replacing all or part of the ethylene glycol groups of the PET polyester with a diol monomer selected from the group consisting of isosorbide, 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, diethylene glycol, 1,2-propylene glycol, neopentyl glycol, 1,3-propylene glycol, 1,4-butanediol and mixtures thereof,

[0081] The proviso is that not all terephthalic acid groups and not all ethylene glycol groups may be substituted simultaneously.

[0082] PET polyester is prepared by polymerization of monomers ethylene glycol and terephthalic acid. Modified PET polyester can be prepared in three different ways. First, modified PET polyester can be prepared by polymerization of monomers ethylene glycol, terephthalic acid and one or more other comonomers, the one or more other comonomers being diacid monomers and / or diol monomers, thereby producing diacid modification, diol modification or diacid / diol modification. Second, modified PET polyester can be prepared by polymerization of monomers ethylene glycol and one or more other comonomers, the one or more other comonomers being one or more diacid monomers and optionally one or more diol monomers. Third, modified PET polyester can be prepared by polymerization of monomers terephthalic acid and one or more other comonomers, the one or more other comonomers being one or more diol monomers and optionally one or more diacid monomers. In all cases, the diacid monomer is selected from the group consisting of adipic acid, succinic acid, isophthalic acid, furandicarboxylic acid, phthalic acid, 4,4'-biphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and mixtures thereof, and the diol monomer is selected from the group consisting of isosorbide, 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, diethylene glycol, 1,2-propylene glycol, neopentyl glycol, 1,3-propylene glycol, 1,4-butanediol, and mixtures thereof.

[0083] In some embodiments, the polymer in the resin is PET polyester. PET polyester is prepared by the reaction of ethylene glycol and terephthalic acid. In a preferred embodiment, the polyester is PET polyester.

[0084] In some embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of ethylene glycol with terephthalic acid and a comonomer 1,4-cyclohexanedimethanol. In other embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of ethylene glycol with terephthalic acid and a comonomer isophthalic acid. In other embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of ethylene glycol with terephthalic acid and a comonomer 2,2,4,4-tetramethyl-1,3-cyclobutanediol. In other embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of terephthalic acid with 1,4-cyclohexanedimethanol. In other embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of terephthalic acid, isophthalic acid, and 1,4-cyclohexanedimethanol. In other embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of ethylene glycol, terephthalic acid, and 2,5-furandicarboxylic acid.

[0085] In a preferred embodiment, the polymer in the resin is poly(terephthalic acid-co-isophthalic acid) polyester. Poly(terephthalic acid-co-isophthalic acid) polyester is prepared by the reaction of ethylene glycol, terephthalic acid and isophthalic acid. In a preferred embodiment, the polymer in the resin is a modified PET polyester, i.e., poly(terephthalic acid-co-isophthalic acid) polyester. The amount of isophthalic acid in poly(terephthalic acid-co-isophthalic acid) polyester is generally 0.5 mol% to 12 mol%, preferably 1 mol% to 3 mol%.

[0086] The chemical composition of poly(terephthalate-co-isophthalate) polyester, i.e., the amount of isophthalic acid in poly(terephthalate-co-isophthalate) polyester, can be determined according to “Martínez de Ilarduya, A.; Kint, DP; Guerra, S. Sequence Analysis of Poly(ethylene terephthalate-co-isophthalate)Copolymers by 13C NMR. The method described in "Macromolecules" (2000, 33, 4596-4598) is characterized by carbon 13 nuclear magnetic resonance spectroscopy (13C NMR). Therefore, the amount of isophthalic acid can be measured using this C NMR method.

[0087] An important characteristic of PET is the intrinsic viscosity (IV). The intrinsic viscosity is measured in dl / g and is derived by extrapolating the relative viscosity to zero concentration. This depends on the length of the PET polymer chains. The longer the polymer chains, the more entanglements there are between the chains, and therefore the higher the viscosity. During the polymerization process, the average length of a particular batch of PET resin can be controlled.

[0088] The intrinsic viscosity (IV) of PET can be measured according to ASTM D4603.

[0089] High IV homopolymer and copolymer PET compositions are difficult to process in injection molding due to their high viscosity.

[0090] In some embodiments, the IV of the PET polyester ranges from 0.6 dl / g to 1.1 dl / g, such as from 0.7 dl / g to 0.9 dl / g, preferably from 0.75 dl / g to 0.85 dl / g.

[0091] In a preferred embodiment, the modified PET polyester is bottle grade PET. The term "bottle grade" is well known in the art and refers to a PET raw material that can be easily processed into bottles. In most embodiments, "bottle grade" PET is made from poly (ethylene terephthalate-co-isophthalate) polyester containing 1 mol% to 3 mol% isophthalic acid. In bottle grade PET, the IV of non-carbonated water is generally in the range of 0.70 dl / g to 0.78 dl / g, and the IV of carbonated water is generally in the range of 0.78 dl / g to 0.85 dl / g.

[0092] Suitable examples of PET grades that are also commercially available include bottle grades EASTLON PET CB-600, CB-602 and CB-608 supplied by Far Eastern New Century (FENC), commercial grade post-consumer rPET CB-602R supplied by FENC, partially bio-based bottle grade PET CB-602AB supplied by FENC, and homopolymer PET grade 6020 supplied by Invista.

[0093] In some embodiments, the polymer in the resin is a modified PET polyester, which is prepared by the reaction of ethylene glycol with terephthalic acid and the comonomer 1,4-cyclohexanedimethanol. In some embodiments, the polymer in the resin is poly(ethylene terephthalate-co-1,4-cyclohexanedimethanol) polyester, also known as ethylene glycol-modified polyethylene terephthalate or PETG. In a preferred embodiment, the polyester is a modified PET polyester, i.e. PETG. The amount of 1,4-cyclohexanedimethanol in PETG is typically 0.1 mol%-25 mol%. In other embodiments, the polymer in the resin is ethylene glycol-modified poly(cyclohexanedimethanol terephthalate), also known as PCTG. In a preferred embodiment, the polyester is a modified PET polyester, i.e. PETG. The amount of 1,4-cyclohexanedimethanol in PETG is typically 25 mol%-49.99 mol%.

[0094] In other embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of ethylene glycol with terephthalic acid and the comonomer 2,2,4,4-tetramethyl-1,3-cyclobutanediol. In some embodiments, the polymer in the resin is poly(ethylene terephthalate-co-2,2,4,4-tetramethyl-1,3-butanediol), also known as PETT.

[0095] In other embodiments, the polymer in the resin is a modified PET polyester made by the reaction of terephthalic acid with 1,4-cyclohexanedimethanol. In some embodiments, the polymer in the resin is poly(cyclohexanedimethanol terephthalate), also known as PCT.

[0096] In other embodiments, the polymer in the resin is a modified PET polyester prepared by the reaction of terephthalic acid, isophthalic acid, and 1,4-cyclohexanedimethanol. In some embodiments, the polymer in the resin is isophthalic acid-modified poly(cyclohexanedimethanol terephthalate), also known as PCTA. The amount of isophthalic acid is typically 0.1 mol% to 50 mol%, more typically 0.1 mol% to 5 mol%.

[0097] In some embodiments, the polymer in the resin is poly(ethylene furandicarboxylate-co-ethylene terephthalate) polyester. Poly(ethylene furandicarboxylate-co-ethylene terephthalate) polyester is prepared by the reaction of ethylene glycol, terephthalic acid and 2,5-furandicarboxylic acid. The amount of 2,5-furandicarboxylic acid in the modified PET polyester is generally 0.5 mol% to 12 mol%, preferably 1 mol% to 3 mol%.

[0098] In some embodiments, the polymer in the resin is polyethylene furandicarboxylate polyester, also known as PEF. Polyethylene furandicarboxylate polyester is prepared by the reaction of ethylene glycol with furandicarboxylic acid. In a preferred embodiment, the polyester is a modified PET polyester, i.e., PEF.

[0099] In one embodiment, the polymer in the resin is a polyacrylate. As used herein, the term "polyacrylate" includes any polymer prepared by polymerization of acrylate monomers, such as acrylic acid, alkyl-substituted acrylic acid, or esters or salts thereof.

[0100] Preferred acrylate monomers include acrylic acid, methyl acrylate, ethyl acrylate, propyl acrylate, methyl methacrylate, methyl ethyl acrylate, and ethyl methacrylate.

[0101] In a preferred embodiment, the polyacrylate may be selected from the group consisting of polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polymethyl methacrylate and polyethyl methacrylate. In a particularly preferred embodiment, the polyacrylate is polymethyl methacrylate (PMMA).

[0102] In one embodiment, the polymer in the resin is polystyrene. As used herein, the term "polystyrene" includes polymers made by polymerization of the monomer styrene. The term also includes copolymers made by copolymerization of the monomer styrene with one or more monomers selected from the group consisting of butadiene, ethylene and acrylonitrile. Thus, the term includes acrylonitrile butadiene styrene (ABS), which is made of polystyrene acrylonitrile, also known as SAN, which is emulsion polymerized or bulk polymerized with polybutadiene, whereby the polybutadiene is effectively encapsulated or dispersed in the SAN matrix.

[0103] In a preferred embodiment, the polystyrene is selected from the group consisting of polystyrene acrylonitrile (SAN), styrene butadiene copolymers and acrylonitrile butadiene styrene (ABS). Styrene butadiene copolymers include block copolymers such as styrene-butadiene copolymers, styrene-butadiene-styrene copolymers (SBS), butadiene block copolymers (SBC) and styrene-ethylene-butylene-styrene copolymers (SEBS).

[0104] In a preferred embodiment, the polymer is selected from the group consisting of polyethylene terephthalate (PET), poly(ethylene terephthalate-co-2,2,4,4-tetramethyl-1,3-butylene glycol ester) (PETT), poly(ethylene terephthalate-co-1,4-cyclohexanedimethanol ester) (PETG) and polymethyl methacrylate (PMMA). In an even more preferred embodiment, the polymer is selected from the group consisting of polyethylene terephthalate (PET) polyester and polymethyl methacrylate (PMMA).

[0105] The resin further comprises an impact modifier. As used herein, the term "impact modifier" refers to an agent that increases the impact toughness of the produced toy building elements. The impact toughness is measured using the Charpy V-notch test according to ISO 179-1.

[0106] The impact modifier may be a reactive impact modifier, a non-reactive impact modifier, or a mixture thereof.

[0107] As used herein, the term "reactive impact modifier" refers to an impact modifier having functionalized end groups. These functionalized end groups serve two purposes: 1) to bond the impact modifier to the polymer matrix; 2) to alter the interfacial energy between the polymer matrix and the impact modifier to enhance dispersibility. Preferred examples of such functionalized end groups include glycidyl methacrylate, maleic anhydride, and carboxylic acids.

[0108] In a preferred embodiment, the reactive impact modifier is a copolymer of formula X / Y / Z, wherein X is an aliphatic or aromatic hydrocarbon polymer having 2-8 carbon atoms, Y is a moiety comprising an acrylate or methacrylate having 3-6 and 4-8 carbon atoms, respectively, and Z is a moiety comprising methacrylic acid, glycidyl methacrylate, maleic anhydride, or a carboxylic acid.

[0109] In a preferred embodiment, the reactive impact modifier can be described by the following formula:

[0110]

[0111] in

[0112] n is an integer from 1 to 4,

[0113] m is an integer from 0 to 5,

[0114] k is an integer from 0 to 5,

[0115] R is an alkyl group of 1 to 5 carbon atoms or 1 hydrogen atom.

[0116] X accounts for 40-90 wt % of the impact modifier, Y accounts for 0-50 wt %, such as 10-40 wt %, preferably 15-35 wt %, most preferably 20-35 wt %, and Z accounts for 0.5-20 wt %, preferably 2-10 wt %, most preferably 3-8 wt % of the reactive impact modifier.

[0117] In other embodiments, X comprises 70 wt % to 99.5 wt %, preferably 80 wt % to 95 wt %, most preferably 92 wt % to 97 wt %, Y comprises 0 wt % of the impact modifier, and Z comprises 0.5 wt % to 30 wt %, preferably 5 wt % to 20 wt %, most preferably 3 wt % to 8 wt % of the reactive impact modifier.

[0118] Suitable examples of specific reactive impact modifiers that can be used in the resins of the present invention include ethylene-vinyl acrylate-glycidyl methacrylate and ethylene-butyl acrylate-glycidyl methacrylate. Commercially available impact modifiers include Paraloid TM EXM-2314 (acrylic acid copolymer from Dow Chemical Company), AX8700, AX8900、Lotader AX8950 and AX8840 (manufactured by Arkema) and PTW (manufactured by DuPont).

[0119] Other suitable examples of specific reactive impact modifiers that can be used in the resins of the present invention include anhydride-modified vinyl acrylates. Commercially available impact modifiers include 3210, 3410, 4210, 3430, 4402, 4503, 4613, 4700, 5500, 6200, 8200, HX8210, HX8290, LX4110, TX8030 (manufactured by Arkema), 21E533, 21E781, 21E810 and 21E830 (manufactured by DuPont).

[0120] In other embodiments, the reactive impact modifier is a modified ethylene vinyl acetate, e.g. 1123 or 1124 (manufactured by DuPont), acid-modified vinyl acrylate, e.g. 2002 or 2022 (manufactured by DuPont), modified vinyl acrylates, e.g. 22E757, 22E780 or 22E804 (manufactured by DuPont), anhydride-modified ethylene vinyl acetate, e.g. 30E670, 30E671, 30E753 or 30E783 (manufactured by DuPont), and acid / acrylate modified ethylene vinyl acetate, e.g. 3101 or 3126 (manufactured by DuPont), anhydride-modified ethylene vinyl acetate, e.g. E418, 3810, 3859, 3860 or 3861 (manufactured by DuPont), anhydride-modified ethylene vinyl acetate, e.g. 3930 or 39E660 (manufactured by DuPont), and anhydride-modified high-density polyethylene, e.g. 4033 or 40E529 (manufactured by DuPont), anhydride-modified linear low-density polyethylene, e.g. 4104, 4105, 4109, 4125, 4140, 4157, 4164, 41e556, 41E687, 41E710, 41E754, 41E755, 41E762, 41E766, 41E850, 41E865 or 41E871 (manufactured by DuPont), anhydride-modified low-density polyethylene, e.g. 4206, 4208, 4288 or 42E703 (manufactured by DuPont) or anhydride-modified polypropylene, e.g. 50E571, 50E662, 50E725, 50E739, 50E803 or 50E806 (manufactured by DuPont).

[0121] Other suitable reactive impact modifiers include maleic anhydride grafted impact modifiers. Specific examples of such reactive impact modifiers include chemically modified vinyl acrylate copolymers, such as A560 (manufactured by DuPont), anhydride-modified polyethylene, e.g. E158 (manufactured by DuPont), anhydride-modified polyethylene resins, such as E564 or E589 or E226 or E528 (manufactured by DuPont), anhydride-modified high-density polyethylene, e.g. E100 or E265 (manufactured by DuPont), anhydride-modified ethylene copolymers, such as N525 (manufactured by DuPont), or chemically modified propylene copolymers, such as E353 (manufactured by DuPont).

[0122] Still other suitable reactive impact modifiers include ethylene-acid copolymer resins, such as ethylene-methacrylic acid (EMAA)-based copolymers and ethylene-acrylic acid (EAA)-based copolymers. Specific examples of ethylene-methacrylic acid-based copolymer impact modifiers include 403, 407HS, 411HS, 0609HSA, 0903, 0903HC, 908HS, 910, 910HS, 1202HC, 599, 699, 925, 960 (manufactured by DuPont). Specific examples of the ethylene-acrylic acid-based copolymer include 30707, 30907, 31001, 3990, AE (manufactured by DuPont). Other specific examples of ethylene-acrylic acid (EAA)-based copolymers include Escor TM 5000, Escor TM 5020、Escor TM 5050、Escor TM 5080、Escor TM 5100, Escor TM 5200 and Escor TM 6000 (manufactured by ExonMobile Chemical).

[0123] Other suitable reactive impact modifiers include ionomers of ethylene acid copolymers. Specific examples of such impact modifiers include 1601, 1601-2, 1601-2LM, 1605, 8150, 8320, 8528 and 8660 (manufactured by DuPont).

[0124] In other embodiments, the reactive impact modifier is a methacrylate-silicone / acrylate graft copolymer. The "methacrylate" of the graft copolymer can be one selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, and butyl methacrylate. The "silicone / acrylate" in the graft copolymer refers to a polymer obtained by polymerizing a mixture of silicone monomers and acrylate monomers. The silicone monomer can be selected from the group consisting of dimethylsiloxane, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, trimethyltriphenylcyclotetrasiloxane, tetramethyltetraphenylcyclotetrasiloxane, and octaphenylcyclotetrasiloxane. The alkyl monomer can be selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, and butyl methacrylate. The graft copolymer is in the form of a core-shell rubber, with a grafting rate of 5wt% to 90wt%, a core glass transition temperature of -150°C to -20°C, and a shell glass transition temperature of 20°C to 200°C. In one embodiment of the present invention, the graft copolymer is a methyl methacrylate-silicone / butyl acrylate graft copolymer. Specific examples include S-2001, S-2100, S-2200 and S-2501 manufactured by Mitsubishi Rayon Co., Ltd.

[0125] Other suitable reactive impact modifiers include the siloxane polymers mentioned in US 4,616,064, which contain siloxane units and at least one of carbonate, urethane or amide units.

[0126] Suitable reactive and non-reactive impact modifiers also include those mentioned in paragraphs

[0043] to

[0072] of WO 2018 / 089573.

[0127] As used herein, the term "non-reactive impact modifier" refers to an impact modifier that does not have functionalized end groups and is therefore unable to form covalent chemical bonds with the polymer matrix. Non-reactive impact modifiers are typically dispersed into the polymer matrix by intensified compounding, but may agglomerate downstream of the compounder.

[0128] Non-reactive impact modifiers can adopt a unique core-shell structure. This structure is obtained by copolymerization of a hard shell around a soft rubber core, and because this structure is usually obtained by emulsion copolymerization, it provides a well-defined particle size, which in turn leads to a well-controlled mixed morphology.

[0129] Suitable examples of non-reactive core-shell impact modifiers include those mentioned in US 5,409,967, i.e. core-shell impact modifiers whose core consists mainly of a rubbery core polymer (e.g., a copolymer containing a diene (preferably 1,3-diene)) and whose shell polymer consists mainly of a vinyl aromatic monomer (e.g., styrene and hydroxyalkyl (meth) acrylate), or in the alternative, another functional monomer that functions in a manner similar to hydroxyalkyl (meth) acrylate. Other suitable examples include impact modifiers having a soft rubber core (e.g., a butadiene core, an acrylic core, or a silicone acrylic core) and a shell made of polymethyl methacrylate (PMMA).

[0130] In some embodiments, the reactive impact modifier has a functionalized end group selected from the group consisting of glycidyl methacrylate, maleic anhydride, and carboxylic acid. In a preferred embodiment, the functional group of the reactive impact modifier is glycidyl methacrylate.

[0131] In some embodiments, the reactive impact modifier has a functionalized end group selected from the group consisting of glycidyl methacrylate, maleic anhydride, and carboxylic acid, while the non-reactive impact modifier is a core-shell impact modifier. In a preferred embodiment, the reactive impact modifier has a functionalized end group that is glycidyl methacrylate, while the non-reactive impact modifier is a core-shell impact modifier.

[0132] In some embodiments, the non-reactive impact modifier is a core-shell impact modifier. In a preferred embodiment, the non-reactive impact modifier is a core-shell impact modifier having a butadiene core, an acrylic core or a silicone acrylic core and a shell made of polymethyl methacrylate (PMMA).

[0133] In some embodiments, the reactive impact modifier has a functionalized end group selected from the group consisting of glycidyl methacrylate, maleic anhydride, and carboxylic acid, while the non-reactive impact modifier is an ethylene-acrylate copolymer. In a preferred embodiment, the reactive impact modifier has a functionalized end group that is glycidyl methacrylate, while the non-reactive impact modifier is an ethylene-acrylate copolymer.

[0134] In some embodiments, the total amount of impact modifier in the resin is in the range of 1 wt% to 30 wt% based on the total weight of the resin. In some embodiments, the total amount of impact modifier is in the range of 2 wt% to 25 wt%, more preferably 3 wt% to 20 wt% or 4 wt% to 15 wt%, or even more preferably 5 wt% to 15 wt%, based on the total weight of the resin.

[0135] In one embodiment, the resin is free of glass, glass microspheres and / or glass fibers. In one embodiment, the resin is free of fibers. In one embodiment, the resin is free of inorganic reinforcements, such as aluminum silicate, asbestos, talc, mica, and calcium carbonate. In one embodiment, the resin is free of organic reinforcements, such as aramid fibers, carbon nanotubes, graphene, and graphite. In one embodiment, the resin is free of glass and fibers.

[0136] In one embodiment, the resin further comprises one or more fillers, the amount of which is up to 5 wt %, such as 0.1 wt % to 5 wt %, more preferably 0.2 wt % to 4 wt %, and most preferably 0.5 wt % to 3 wt %, based on the total weight of the resin. The one or more fillers may be inorganic particulate materials or nanocomposites or mixtures thereof.

[0137] Suitable examples of inorganic particulate materials include inorganic oxides, such as glass, MgO, SiO2, TiO2 and Sb2O3; hydroxides, such as Al(OH)3 and Mg(OH)2; salts, such as CaCO3, BaSO4, CaSO4 and phosphates; silicates, such as talc, mica, kaolin, wollastonite, montmorillonite, nanoclay, feldspar and asbestos; metals, such as boron and steel; carbon-graphite, such as carbon fibers, graphite fibers and flakes, carbon nanotubes and carbon black. Suitable examples of inorganic particulate materials also include surface treated and / or surface modified SiO2 and TiO2, such as TiO2 surface modified with alumina.

[0138] Suitable examples of nanocomposites include clay-filled polymers, such as clay / low-density polyethylene (LDPE) nanocomposites, clay / high-density polyethylene (HDPE) nanocomposites, acrylonitrile-butadiene-styrene (ABS) / clay nanocomposites, polyimide (PI) / clay nanocomposites, epoxy resin / clay nanocomposites, polypropylene (PP) / clay nanocomposites, polymethyl methacrylate (PMMA) / clay nanocomposites and polyvinyl chloride (PVC) / clay nanocomposites; alumina-filled polymers, such as epoxy resin / alumina nanocomposites, PMMA / alumina nanocomposites, PI / alumina nanocomposites, PP / alumina nanocomposites, LDPE / alumina nanocomposites, and polyvinyl chloride (PVC) / clay nanocomposites. Composites and cross-linked polyethylene (XLPE) / alumina nanocomposites; barium titanate filled polymers, such as HDPE / barium titanate nanocomposites and polyetherimide (PEI) / barium titanate nanocomposites; silica filled polymers, such as PP / silica nanocomposites, epoxy resin / silica nanocomposites, PVC / silica nanocomposites, PEI / silica nanocomposites, PI / silica nanocomposites, ABS / silica nanocomposites and PMMA / silica nanocomposites; and zinc oxide filled polymers, such as LDPE / zinc oxide nanocomposites, PP / zinc oxide nanocomposites, epoxy resin / zinc oxide nanocomposites and PMMA / zinc oxide nanocomposites.

[0139] In step b), the resin is processed to produce an amorphous toy building element. The amorphous toy building element can be produced by injection molding the resin, extruding the resin or by additive manufacturing of the resin. The preferred type of processing is injection molding. The toy building element can also be produced by a combination of injection molding and additive manufacturing, wherein the injection molded toy building element is further processed by additive manufacturing other parts of the toy building element on top of the injection molded toy building element (see, for example, US2015 / 0190724 A1).

[0140] In some embodiments, the toy building elements are manufactured by injection molding.

[0141] In such embodiments, the impact modifier is mixed with the polymer during the feeding process of the injection molding machine.

[0142] In other embodiments, the impact modifier is mixed with the polymer and the mixture is then fed into an injection molding machine. Mixing can be done by dry blending or compounding.

[0143] In some embodiments, the impact modifier is dry blended with the polymer and then fed into the injection molding machine.

[0144] In other embodiments, the impact modifier is mixed with the polymer by compounding and then fed to the injection molding machine.

[0145] In some embodiments, the impact modifier is compounded with the polymer with thorough mixing to ensure adequate dispersion and then fed directly into the injection molding machine.

[0146] In other embodiments, the polymer can be mixed with the impact modifier into a masterbatch, which is then mixed with the rest of the resin during the feed process of the injection molding machine.

[0147] Additives such as fillers, nucleating agents, anti-hydrolysis additives, mold release agents, lubricants, UV stabilizers, flame retardants, chain extenders, processing stabilizers, antioxidants and colorants or pigments can be added and mixed with the impact modifier and polyester before or during feeding of the injection molding machine.

[0148] Injection molded toy building elements are made of amorphous materials. Those skilled in the art know how to control the injection molding process to obtain injection molded products of amorphous materials. Typically, the temperature of the polymer material in the injection molding barrel is higher than the melting temperature. The melt enters a cooler mold to solidify the material. The mold temperature can be higher or lower than the glass transition temperature (Tg) of the polymer material. Temperatures below Tg are conducive to the transition to an amorphous final material. Those skilled in the art know that the faster the cooling rate of the injected material, the more amorphous material is obtained. Fast cooling rates are typically obtained by keeping the mold temperature as low as possible and preferably significantly lower than the glass transition temperature of the injected material.

[0149] In step c), the amorphous toy building element is heat treated for at least 15 minutes at a heat treatment temperature of at least 40° C. The upper limit of the heat treatment temperature is 20° C. below the onset of the glass transition temperature (Tg) of the impact modified amorphous material.

[0150] Unlike annealing, the heat treatment according to the present invention is performed at the glass transition temperature of the material. This is important because heat treating the material at or above the glass transition temperature does not affect functional durability and enthalpy relaxation. The temperature difference between the starting temperature of the glass transition temperature according to the present invention and the heat treatment temperature is to avoid warping and mold stress release of the amorphous component due to the heat treatment. The functional durability improvement rate is related to the difference between the exposed heat treatment temperature and the glass transition temperature of the heat treated material. By getting closer to the glass transition temperature of the heat treated material, the functional durability improvement rate of the material is increased.

[0151] The term "glass transition temperature (Tg)" as used herein refers to the temperature at which the hard glass state of an amorphous material changes to a rubbery state. This transition usually occurs within a certain temperature range. Therefore, the term "onset temperature of the glass transition temperature" as used herein refers to the temperature at which the transition process begins.

[0152] The onset temperature of the glass transition temperature depends on the specific polymer material. For example, the Tg onset temperature of PET is about 80°C, the Tg onset temperature of PETG is about 80°C, the Tg onset temperature of PETT is about 90°C, the Tg onset temperature of PCTT is about 110°C, and the Tg onset temperature of the SAN phase in ABS is about 100°C.

[0153] In some embodiments, the upper limit of the heat treatment temperature is in the range of 20°C-45°C lower than the onset temperature of the glass transition temperature (Tg), for example, in the range of 20°C-40°C lower than the onset temperature of the glass transition temperature (Tg), or in the range of 25°C-35°C lower than the onset temperature of the glass transition temperature (Tg), provided that the lower limit of the heat treatment temperature is 40°C or more. In a preferred embodiment, the upper limit of the heat treatment temperature is 30°C lower than the onset temperature of the glass transition temperature (Tg).

[0154] In one embodiment, the heat treatment temperature is at least 42°C, such as at least 44°C, or at least 46°C, or at least 48°C, or at least 50°C.

[0155] The heat treatment time is at least 15 minutes. In theory, there is no upper limit to the heat treatment time. Typically, the heat treatment time of the amorphous toy building element is from 15 minutes to 672 hours (4 weeks), for example from 1 hour to 168 hours (1 week) or from 1 hour to 24 hours. In a preferred embodiment, the heat treatment time of the amorphous toy building element is from 1 hour to 12 hours, more preferably from 4 hours to 10 hours, most preferably 8 hours.

[0156] In step d), the heat-treated toy building element is cooled to ambient temperature. This cooling can be achieved by storing the element at ambient conditions or actively cooling it to a temperature below ambient conditions. This can be done in ambient atmosphere or in water to shorten the time it takes for the element to reach ambient temperature. Once ambient temperature has been reached, the toy building element can be packaged and stored, or it can be sent to a store for sale.

[0157] A second aspect of the invention relates to a toy building element with increased functional durability, made from an impact-modified amorphous material comprising a polymer and an impact modifier and having an enthalpy relaxation of at least 0.3 J / g (e.g. in the range of 0.3 J / g to 4 J / g) and a shrinkage of a maximum of 0.2%.

[0158] In a preferred embodiment, the toy building element is produced by the method according to the invention.

[0159] The amount of polymer in the impact-modified amorphous material is preferably at least 50% by weight, based on the total weight of the impact-modified amorphous material.

[0160] In other embodiments, the amount of polymer in the impact-modified amorphous material is at least 60 wt % based on the total weight of the impact-modified amorphous material. In a preferred embodiment, the amount of polymer in the impact-modified amorphous material is at least 70 wt %, such as at least 85 wt %, or at least 90 wt % based on the total weight of the impact-modified amorphous material.

[0161] In another embodiment, the amount of polymer in the impact-modified amorphous material is in the range of 50 wt% to 99 wt% based on the total weight of the impact-modified amorphous material. In other embodiments, the amount of polymer in the impact-modified amorphous material is in the range of 60 wt% to 97 wt% or 70 wt% to 95 wt% based on the total weight of the impact-modified amorphous material. In a preferred embodiment, the amount of polymer in the impact-modified amorphous material is in the range of 75 wt% to 95 wt%, such as 80 wt% to 95 wt%, based on the total weight of the impact-modified amorphous material.

[0162] The polymer in the impact-modified amorphous material can be a bio-based polymer, a mixed bio-based polymer, or a petroleum-based polymer, or a mixture thereof. These terms are defined above, and also include recycled polymers and recycled materials comprising bio-based polymers, mixed bio-based polymers, or petroleum-based polymers as described above.

[0163] In a preferred embodiment, the polymer is selected from the group consisting of polyester, polyacrylate and polystyrene. These terms are as defined above. In a preferred embodiment, the polymer is selected from the group consisting of polyethylene terephthalate (PET), poly(ethylene terephthalate-co-2,2,4,4-tetramethyl-1,3-butylene glycol ester) (PETT), poly(ethylene terephthalate-co-1,4-cyclohexanedimethanol ester) (PETG) and polymethyl methacrylate (PMMA). In an even more preferred embodiment, the polymer is selected from the group consisting of polyethylene terephthalate (PET) polyester and polymethyl methacrylate (PMMA).

[0164] The toy building element made of the impact-modified amorphous material also comprises an impact modifier as described above. The impact modifier can be a reactive impact modifier, a non-reactive impact modifier, or a mixture thereof. In one embodiment, the amount of the impact modifier in the impact-modified amorphous material is in the range of 1 wt % to 30 wt % based on the total weight of the impact-modified amorphous material. In some embodiments, the amount of the impact modifier is in the range of 2 wt % to 25 wt %, more preferably 3 wt % to 20 wt % or 4 wt % to 15 wt % or even more preferably 5 wt % to 15 wt % based on the total weight of the impact-modified amorphous material.

[0165] Example

[0166] In the following examples, it is described how samples were prepared, heat treated and evaluated by different tests. Three of the tests are the "Charpy V-notch test", the "Shrinkage test" and the "Enthalpy relaxation test".

[0167] Charpy V-notch test

[0168] Cut the relevant material to be tested according to ISO 179-1:2010 with a notch cutter (ZNO, Zwick, Germany) with a notch tip diameter of 0.5 mm according to ISO 179-1-A. 3 , molded plastic bars with dimensions of B x W x L. Notched specimens were placed in a V-notch opposite the pendulum and tested in a pendulum impact machine (HOT, Zwick, Germany) according to the principle described in ISO 179-1:2010.

[0169] Shrinkage test

[0170] The shrinkage is the average value of the length and width of the ISO 527-1BA tensile element relative to the initial dimensions measured by calipers according to the following formula:

[0171]

[0172] Where t=x is the size after a period of heat treatment, and t=0 is the initial size of the component.

[0173] Enthalpy relaxation test (see Example 7 and Example 9)

[0174] The enthalpy relaxation values ​​were measured during heating of 20 mg of flat-cut samples to 300°C at the glass transition temperature (Tg) as described in “E. Andersen, R. Mikkelsen, S. Kristiansen, M. Hinge, Accelerated physical ageing of poly(l,4-cyclohexylenedimethylene-co-2,2,4,4-tetramethyl-l,3-cyclobutanediol terephthalate), RSC Adv. 2019, 9, 14209–14219”.

[0175] Example 1. Preparation and heat treatment of injection molded samples

[0176] In order to evaluate the stress relaxation properties of heat treated and non-heat treated injection molded polymer materials according to the present invention, stress relaxation experiments were performed. Stress relaxation experiments measure the stress exerted on a specimen under constant strain.

[0177] Stress relaxation measurements were performed on 1BA ISO 527-2:2012 injection molded specimens in uniaxial tension on a Zwick-Roell Kappa Multistation 5x10 kN.

[0178] Charpy V-notch impact toughness measurements were performed as described above.

[0179] The injection molded components were inserted into an artificial climate chamber (HPP260, Memmert, GER) controlled at a given temperature and 50% RH for a period of time, removed and left for at least 24 hours before testing. The components were then inserted into a tensile fixture and the device was allowed to control the temperature of the test chamber. The components were left in the tensile fixture until the temperature reached equilibrium. The materials studied are listed in Table 1 below.

[0180]

[0181] Table 1: Polymers and impact modifiers in the studied materials

[0182] Example 2: Stress Relaxation Measurements of Heat Treated and Unheat Treated Injection Molded Samples

[0183] After temperature equilibrium, the sample prepared in Example 1 was loaded to 1% strain at 1 mm / min, and the stress of the sample was measured for 48 hours to obtain the stress-strain curve of the stress relaxation experiment. The strain was determined by measuring the displacement between two reference points using a video extensometer, and the stress was measured in the load cell of the equipment.

[0184] Figure 1 The stress-strain curves of rPET (10% PARALOID EXL, 2.5% ELVALOY) before and after heat treatment at 50°C for 8 hours are shown. From this figure, it can be seen that the impact-modified rPET exhibits obvious stress relaxation behavior by reducing stress when the strain is kept constant. This stress loss over time is significantly reduced after heat treatment.

[0185] Quantification of material stress relaxation can be determined by evaluating the stress drop over a specified test period at a constant strain. For example, at 1% strain, the difference between the stress measured at t=0 hours and t=48 hours. Calculating the relative reduction in stress during such an experiment can help to compare materials. This is done by normalizing the stress measured during the experiment by the stress when the strain was initially reached, which is equal to the maximum stress during the experiment. This can be done according to the following formula:

[0186]

[0187] Figure 2 A graph generated using normalized stress data is shown.

[0188] according to Figure 2 , the normalized stress of the experiment at 48 hours shows the degree of stress retention, which is called the relative stress retention rate. In this embodiment, the relative stress retention rates of the heat-treated (8 hours, 50°C) and untreated samples are 69% and 37%, respectively. The higher the relative stress retention rate, the better the stress relaxation and the better the functional durability. The results clearly show that the 8-hour heat treatment significantly improves the relative stress retention rate, thereby improving the functional durability.

[0189] Example 3: Stress relaxation measurements of injection molded samples after different heat treatment times

[0190] It was also investigated how the heat treatment time affects the stress retention. More precisely, injection molded samples made of rPET (10% PARALOIDE XL, 2.5% ELVALOY) were heat treated for 0 hours, 8 hours, 24 hours and 168 hours and investigated.

[0191] The results are as follows Figure 3As shown. It can be clearly seen that by increasing the heat treatment time at constant temperature, the relative stress retention rate increases. This means that by increasing the heat treatment time, the functional durability of the material is improved.

[0192] Example 4: Stress relaxation measurements of injection molded samples made of different polymers

[0193] The stress retention of different samples made from different polymers was also studied. Both unmodified and impact-modified samples were tested. Samples containing rPET and 10% impact modifier were heat treated at 50°C (i.e. 30°C below its glass transition temperature) for 24 hours. Samples containing PMMA and impact modifier were heat treated at 60°C (i.e. 30°C below its glass transition temperature) for 24 hours. Samples containing PETT and no modifier were heat treated at 60°C (i.e. 30°C below its glass transition temperature) for 24 hours. Samples containing PETG and no modifier were heat treated at 50°C (i.e. 30°C below its glass transition temperature) for 24 hours.

[0194] The results are as follows Figure 4 As shown. It can be seen that heat treatment improves the relative stress retention of impact-modified rPET and PMMA and unmodified PETG and PETT (stress retention changes from 4% to 38%).

[0195] Example 5: Stress Relaxation Measurements of Injection Molded Samples Containing Different Amounts of Impact Modifier

[0196] The stress retention of rPET samples containing different concentrations of impact modifiers was also studied. Figure 5 As shown. It can be seen that heat treatment improves the stress retention of rPET at various impact modification levels.

[0197] Example 6: Charpy V-notch impact toughness measurements of injection molded samples containing different amounts of impact modifier

[0198] The Charpy V-notch impact toughness of rPET samples containing different concentrations of impact modifiers was studied. Figure 6 As shown. It can be seen that the increase in the concentration of impact modifier improves the impact toughness of rPET. Improving the impact toughness of rPET is required for durable applications.

[0199] Example 7: Impact toughness and enthalpy relaxation measurements of injection molded samples

[0200] The effect of heat treatment time on impact toughness and enthalpy relaxation was also studied. More precisely, injection molded samples made of rPET (10% PARALOID EXL, 2.5% ELVALOY) were heat treated for 0 minutes, 15 minutes, 30 minutes, 8 hours and 24 hours and studied. The heat treatment temperature was 60°C, which is 20°C lower than the glass transition temperature of rPET.

[0201] The results are as follows Figure 7 As shown in Figure 2, the enthalpy relaxation increases strongly within the first 30 minutes of heat treatment. After that, the enthalpy relaxation is still increasing, but not as strongly. After 15 minutes of heat treatment, the enthalpy relaxation has increased to more than 0.3 J / g.

[0202] Figure 7 The results shown in also show that the impact toughness decreases with increasing enthalpy relaxation. This result is expected, because heat treatment at the glass transition temperature leads to embrittlement of plastic parts that are susceptible to physical aging (such as PET, PMMA and SAN) (for example, explained in "Progress of the Royal Society of Chemistry (RSC Adv.)", 2019, 9, 14209-14219).

[0203] Example 8: Shrinkage Measurement of Injection Molded Samples

[0204] The shrinkage of injection molded samples made of rPET (10% PARALOID EXL, 2.5% ELVALOY) was studied after heat treatment at different temperatures: 50°C (30°C lower than the glass transition temperature of rPET), 55°C (25°C lower than the glass transition temperature of rPET), 60°C (20°C lower than the glass transition temperature of rPET) and 65°C (15°C lower than the glass transition temperature of rPET) for 24 hours.

[0205] The results are as follows Figure 8 The results clearly show that the shrinkage increases with increasing heat treatment temperature. When the heat treatment temperature is 60°C (20°C below the glass transition temperature) or below, the shrinkage is less than 0.2%. When the heat treatment temperature is 65°C (15°C below the glass transition temperature), the shrinkage exceeds 0.9%, which is unacceptable according to the present invention, since the present invention focuses on producing toy building elements with increased functional durability.

[0206] Example 9: Measurement of Charpy V-notch impact toughness and relative stress retention of injection molded samples

[0207] The Charpy V-notch impact toughness and relative stress retention of injection molded samples made of rPET (10% PARALOID EXL, 2.5% ELVALOY) were also studied. The measurements were performed after heat treatment of the injection molded samples for 24 hours at different temperatures: 23°C, 50°C (30°C below the glass transition temperature of rPET), 55°C (25°C below the glass transition temperature of rPET), 60°C (20°C below the glass transition temperature of rPET) and 70°C (10°C below the glass transition temperature of rPET).

[0208] The results are as follows Fig. 9 and Fig.10 shown. Fig. 9 The results of the Charpy V-notch impact toughness test are shown. Fig. 9 The results shown in show that impact toughness decreases with increasing heat treatment temperature up to 60°C (20°C below the glass transition temperature of rPET). Thereafter, impact toughness increases as the glass transition temperature is approached. The loss of impact toughness caused by heat treatment of injection molded samples according to the present invention is not important, as long as the addition of impact modifier to the original polymer material has increased the impact toughness to such a level that the reduction in impact toughness caused by the heat treatment still leaves the impact toughness of the heat treated component at an acceptable level. It is important to note that the present invention focuses on improving stress relaxation properties and that a reduction in impact toughness cannot be avoided; but by ensuring that the starting level is high enough, the loss can be made negligible.

[0209] Fig.10 The results of stress relaxation tests are shown. These results clearly show that heat treatment of the injection molded samples at 50°C and 55°C (25°C and 30°C below the glass transition temperature of rPET, respectively) provides the best stress relaxation, while heat treatment at 65°C (15°C below the glass transition temperature of rPET) provides poor stress relaxation. These results support the finding that an upper heat treatment temperature limit of 20°C below the glass transition temperature will provide acceptable functional durability for injection molded toy building elements.

Claims

1. A method for producing a toy building element with increased functional durability, the toy building element being made of an impact-modified amorphous material having an enthalpy relaxation of at least 0.3 J / g, for example in the range of 0.3 J / g to 4 J / g, and a shrinkage of at most 0.2%, the method comprising the following steps: a) providing a resin comprising a polymer and an impact modifier, b) processing the resin to produce an amorphous toy building element, c) heat treating the amorphous toy building element at a heat treatment temperature of at least 40° C. for at least 15 minutes, and d) cooling the heat-treated toy building element to ambient temperature, The upper limit of the heat treatment temperature in step c is 20° C. lower than the onset temperature of the glass transition temperature (Tg) of the impact-modified amorphous material.

2. The method according to claim 1, wherein: The amount of polymer in the resin is at least 50 wt % based on the total weight of the resin.

3. The method according to any one of claims 1 or 2, wherein: The polymer is selected from the group consisting of polyester, polyacrylate and polystyrene.

4. The method according to any one of claims 1 to 3, wherein: The polymer is selected from the group consisting of polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA).

5. The method according to any one of claims 1 to 4, wherein: The amount of the impact modifier in the resin is 1 wt % to 30 wt % based on the total weight of the resin.

6. The method according to any one of claims 1 to 5, wherein: The impact modifier is a reactive impact modifier, a non-reactive impact modifier or a mixture thereof.

7. The method according to any one of claims 1 to 6, wherein: In step c, the amorphous toy building element is heat treated at a heat treatment temperature 20°C to 45°C lower than the onset temperature of the glass transition temperature of the impact-modified amorphous material, provided that the lower limit of the heat treatment temperature is 40°C or above.

8. The method according to any one of claims 1 to 7, wherein: In step c, the amorphous toy building element is subjected to a heat treatment for a period of 15 minutes to 4 weeks.

9. The method according to any one of claims 1 to 8, wherein: In step b the amorphous toy building element is produced by injection moulding the resin.

10. A toy building element with increased functional durability, made of an impact-modified amorphous material comprising a polymer and an impact modifier and having an enthalpy relaxation of at least 0.3 J / g, such as in the range of 0.3 J / g to 4 J / g, and a shrinkage of a maximum of 0.2%.

11. A toy building element according to claim 10, wherein: The amount of polymer in the impact-modified amorphous material is at least 50 wt % based on the total weight of the impact-modified amorphous material.

12. A toy building element according to any one of claims 10 or 11, wherein The polymer is selected from the group consisting of polyester, polyacrylate and polystyrene.

13. A toy building element according to any one of claims 10 to 12, wherein The polymer is selected from the group consisting of polyethylene terephthalate (PET) polyester and polymethyl methacrylate (PMMA).

14. A toy building element according to any one of claims 10 to 13, wherein The amount of the impact modifier in the impact-modified amorphous material is 1 wt % to 30 wt % based on the total weight of the impact-modified amorphous material.

15. A toy building element according to any one of claims 10 to 14, wherein The impact modifier is a reactive impact modifier, a non-reactive impact modifier or a mixture thereof.

Citation Information

Patent Citations

  • A method for the manufacture of a plastics product and a product made by the method

    US20150190724A1

  • Toy building brick

    US3005282A

  • Polymeric compositions suitable for use in the medical field and comprising a thermoplastic olefin, a siloxane polymer, and an elastomer

    US4616064A

  • Amorphous, aromatic polyester containing impact modifier

    US5409967A

  • Cellulose ester and impact modifier compositions and articles made using these compositions

    WO2018089573A1